Biomimetic hydroxyapatite/collagen composite drives bone niche recapitulation in a rabbit orthotopic model. (March 2019) - Minardi, S.; Taraballi, F.; Cabrera, F.J.; Van Eps, J.; Wang, X.; Gazze, S.A.; Fernandez-Mourev, Joseph S.; Tampieri, A.; Francis, L.; Weiner, B.K.; Tasciotti, E.
Abstract: Synthetic osteoinductive materials that mimic the human osteogenic niche have emerged as ideal candidates to address this area of unmet clinical need. In this study, we evaluated the osteoinductive potential in a rabbit orthotopic model of a magnesium-doped hydroxyapatite/type I collagen ​(MHA/Coll) composite. The composite was fabricated to exhibit a highly fibrous structure of carbonated MHA with 70% (±2.1) porosity and a Ca/P ratio of 1.5 (±0.03) as well as a diverse range of elasticity separated to two distinct stiffness peaks of low (2.35 ​± ​1.16 ​MPa) and higher (9.52 ​± ​2.10 ​MPa) Young's Modulus. Data suggested that these specific compositional and nanomechanical material properties induced the deposition of de novo mineral phase, while modulating the expression of early and late osteogenic marker genes, in a 3D in vitro model using human bone marrow-derived mesenchymal stem cells (hBM-MSCs). When tested in the rabbit orthotopic model, MHA/Col1 scaffold induction of new trabecular bone mass was observed by DynaCT scan, only 2 weeks after implantation. Bone histomorphometry at 6 weeks revealed a significant amount of de novo bone matrix formation. qPCR demonstrated MHA/Coll scaffold full cellularization in vivo and the expression of both osteogenesis-associated genes ( Spp1, Sparc, Col1a1, Runx2, Dlx5 ) as well as hematopoietic ( Vcam1, Cd38, Sele, Kdr ) and bone marrow stromal cell marker genes ( Vim, Itgb1, Alcam ). Altogether, these data provide ​evidence of the solid osteoinductive potential of MHA/Coll and its suitability for multiple approaches of bone regeneration. Highlights: We tested magnesium-doped hydroxyapatite/type I collagen (MHA/Coll) in a biologics-free orthotopic bone regeneration model. MHA/Coll allowed bone formation within 6 weeks in a rabbit orthotopic model. MHA/Coll supported the formation of both an osteogenic and hematopoietic-like niche.